Quality control measures for GWAS - Barrett, Jeffrey (Henry Stewart Talks, 2008)
Unfiltered GWA data lead to false positive associations, SNP and genotype quality control, including imputation, Sample quality control, including related individuals and ethnic outliers, Quality control in the WTCCC, Software for QC of GWA
Archived at 2020/01/15